ISLAMIST MOBILIZATION UNDER MULTI-PARTY SYSTEM IN ALGERIA - Ahmad, Mohammad Wasim (ShodhKosh: Journal of Visual and Performing Arts, 2024)
During the 1980s, as regime capacity to distribute service became constricted. Dissatisfaction with the government performance began to grow in various sectors of the society. The inadequacy of the government’s economic measures to keep up with the need for a fast-rising population, compounded by the mid-to-late 1980s austerity policies, provides ideal ground for Islamist movements. In October 1988, disgruntled youth were among the first to react to the tension, their actions creating a gap in the state’s defences through which Islamists rushed. Following riots in October 1988, Algeria’s government opened the political system overnight in February 1989, after more than two decades of one-party control under the National Liberation Front (FLN). This article follows the new constitution adopted after 1988 riots and consequent end of the one-party system and mentions the acceptance of multi-party system in Algeria. It is also mentioning the political changes that came after the constitutional change, especially the Islamist political upsurge. Subsequently, this article focuses on the various ideological differences within Political Islam, namely, rejectionist, moderate and liberal. Finally, it mentions the rise of Islamist Parties and the electoral and political dilemma of Algerian political elite.